Land-vehicle mems INS/GPS positioning during GPS signal blockage periods - Tan, T. D.; Ha, L. M.; Long, N. T.; Duc, N. D.; Thuy, N. P. (VNU Journal of Science: Mathematics - Physics; Vol 23 No 4, 2007)
Abstract: